2016
DOI: 10.3892/etm.2016.3457
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor α-induced protein-3 protects zinc transporter 8 against proinflammatory cytokine-induced downregulation

Abstract: Abstract. Zinc transporter 8 (ZnT8) is exclusively expressed in the pancreatic islet and is essential for insulin crystallization, hexamerization and secretion. Tumor necrosis factor α-induced protein-3 (TNFAIP3) is a zinc finger protein that serves a major role in the negative feedback regulation of NF-κB signaling in response to multiple stimuli, and is a central regulator of immunopathology. Although the role of TNFAIP3 in diabetes has been extensively studied, its effect on ZnT8 has not been fully elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Our experiments showed that human ␤-cells responded to acute cytokine exposure with a rapid, graded, and reversible down-regulation of the cellular ZnT8 level. These findings are consistent with earlier studies of cytokine-regulated SLC30A8 expression in rodent ␤-cells with some differences in the effects on GSIS and the cellular insulin content (62)(63)(64). We found that cytokine-induced ZnT8 down-regulation did not affect GSIS in human insulinoma cells but strongly correlated with the insulin content.…”
Section: Discussionsupporting
confidence: 93%
“…Our experiments showed that human ␤-cells responded to acute cytokine exposure with a rapid, graded, and reversible down-regulation of the cellular ZnT8 level. These findings are consistent with earlier studies of cytokine-regulated SLC30A8 expression in rodent ␤-cells with some differences in the effects on GSIS and the cellular insulin content (62)(63)(64). We found that cytokine-induced ZnT8 down-regulation did not affect GSIS in human insulinoma cells but strongly correlated with the insulin content.…”
Section: Discussionsupporting
confidence: 93%
“…On another hand, there is a close relationship between down-regulation of zinc transporter expression, zinc homeostasis and inflammatory response, which may contribute to the development of diabetes and DKD 16 , 21 . A previous study has demonstrated that inflammation or TNF-α-induced protein-3 dysfunction may be involved in the pathogenesis of diabetes via ZnT8 expression, besides from pancreatic islet cell apoptosis, in which protects ZnT8 against pro-inflammatory cytokine-induced downregulation 34 . Evidence that TGF-β1 plays significant role in EMT of renal epithelial cells, so we as to focus on the TGF-β1 in effect of ZnT8 on EMT of renal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TNIP1 ( TNF - α induced protein 3 ( TNFAIP3 or A20) interacting protein 1) could be targeted by ENSSSCT00000018610. Overexpression of TNIP1 gene interact with TNFAIP3 to restrict NF-κB activation, then further reduced autoimmunity response by TNF-independent signals 56 and prevented intestine immune and inflammatory diseases 57–59 . Study reported that TNFAIP3 repressed cell apoptosis by TNF and IL-1β , and affected proinflammatory gene expressions by directly acting on TRAF6 signaling molecule 60 .…”
Section: Discussionmentioning
confidence: 99%